THE ROLE OF CUSTOMER RELATIONSHIP MANAGEMENT IN INCREASING CUSTOMER LOYALTY - Hanafiah, Hafidz; Gursida, Hari; Muharam, Hari (Yayasan Education and Social Center, 2025)
Customers are the spearhead in marketing performance in generating profit. In its implementation, a good relationship is needed between customers and the company organization or MSMEs that have the product. The purpose of this study is to describe and analyze the role of customer relationship management as an effort to increase customer loyalty at coffee shop of 27 Serang City Banten. The research method uses a qualitative method. While the data collection technique is through deductive analysis, comparative analysis, and data verification. As well as checking the validity of the findings, namely continuous observation, triangulation testing, and proof of the truth of the data that the researcher has found. The results of the study found that (1) The role of customer relationship management can increase customer loyalty at coffee shop of 27 Serang City Banten through customer loyalty programs starting from planning, implementation, to evaluation of the program according to previously planned customer targets; (2) Customer loyalty at coffee shop of 27 Serang City Banten can be seen from loyal customers with customer visit retention, always recommending to others, and always making repeat purchases.